Reducing the Spectral Emissions of PFC Converters by Anticontrol of Chaos - Marcelle Merhy; Cristina Morel; Eric Chauveau; Mohamed Machmoum (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
Switch-mode power supplies usually emit electromagnetic interferences at the switching frequency and its multiple harmonics. We propose a feedback control method improving switch-mode power supplies electromagnetic compatibility (spectral peaks compliance). Inducing chaos in these systems has recently been suggested as a means of reducing these spectral emissions. Indeed, the application of the classical method of chaos anticontrol to these systems leads the output voltage to have an excessive ripple or an undesirable spectrum, whereas these problems are solved with ours. We propose here a converter, able at the same time to achieve low spectral emission and to maintain a small ripple. The design of this controller is based on the property that chaotified nonlinear systems present many independent chaotic attractors of small dimensions. To confirm the efficiency of this method, a comparison with the anticontrol method is included, together with a numerical example clearly showing the effect of this control.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.2136